Don't get mad, get open. - HEALY, HAZEL (New Internationalist, 2012)
The article looks at computer software developers creating free software. Particular attention is given to Richard Stallman, an advocate for free software programs that can be used, altered, and shared without the involvement of copyright laws. Information is also provided on users' ability to improve the source code that operates free software, as well as the Free Software Foundation (FSF), and the relationship between censorship and online content.